Prevalence of Human Papillomavirus Among Chinese Han and Mongols Minority Women in Inner Mongolia, China: Reflected by Self-Collected Samples in CHIMUST - Guo, Chunlei; Du, Hui; Qu, Xinfeng; Duan, Xianzhi; Li, Jingran; Li, Ruizhen; Jin, Hua; Wang, Chun; Zhao, Chao; Bao, Juncui; Luo, Hongxue; Wei, Lihui; et al. (Frontiers in Public Health, 2022)
Background The disparities of hr-HPV infection among races/ethnicities have not been fully discussed. This study aimed to investigate the difference of hr-HPV infection between Chinese Han and Mongols minority women in Inner Mongolia. Methods Genotyping and histopathology data of Chinese Han and Mongols minority women in Inner Mongolia from Chinese Multi-Center Screening Trial were used to analyze the hr-HPV prevalence, and type-specific distribution in abnormal pathology results. Results The hr-HPV infection rates of Han women was 15.9% while of Mongols was 21.6% (P＜0.001). The most prevalent genotypes in Han women were ranked as HPV-16, -52, -18/-58, -31/-39 and -59 while in Mongols were -16, -31, -58, -18 and -52. When analyzing the age-specific of hr-HPV infection, two peaks were found at age of 40-44 (20.5%) and 55-59 (23.5%) years in Han women while three peaks were observed at age of 30-34 (22.1%), 45-49 (22.9%) and 55-59 (31.8%) years, respectively, in Mongols. HPV-16 accounting for 62.5% and 53.8% of the CINII+ in Han and Mongols respectively. Conclusion The prevalence and distribution of hr-HPV infection based on self-collected HPV testing between the Han and Mongols minority women in Inner Mongolia have been characterized with race/ethnicity differences.